2022
DOI: 10.15587/1729-4061.2022.254090
|View full text |Cite
|
Sign up to set email alerts
|

Increasıng the bıologıcal value of bread through the applıcatıon of pumpkın puree

Abstract: Some vegetables are indispensable for the production of a wide range of bread products, because of their chemical composition. One of the factors hindering their widespread use in the bakery is the insufficient study of their functional properties in the mentioned technological areas. The main goal of the study was a complex analysis of the food value, mineral and vitamin compositions of raw materials and bread with additives, on the example of pumpkin variety «Perekhvatka 69». This is necessary to further sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 4 publications
1
9
0
Order By: Relevance
“…Study [18] found that the addition of 10 % of pumpkin paste to the bread recipe significantly increased the content of β-carotene, thiamine, riboflavin, niacin, and ascorbic acid. The content of mineral elements also increased.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…Study [18] found that the addition of 10 % of pumpkin paste to the bread recipe significantly increased the content of β-carotene, thiamine, riboflavin, niacin, and ascorbic acid. The content of mineral elements also increased.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…The decrease in aroma of tomato puree might be due to escape of some volatile compounds and storage temperature and time. According to Baldwin et al, [12,13,3,5].…”
Section: Aromamentioning
confidence: 99%
“…This vegetable can be consumed in various forms, either as a whole vegetable or as an ingredient of stews, sauces, desserts, jellies, jams, purees and other products, however, the primary form of commercialization is as a fresh vegetable. Nonetheless, pumpkin puree can be found on the market as canned food, ready to be eaten Gurbanova S et al [5].…”
Section: Introductionmentioning
confidence: 99%
“…Study [29] found that pumpkin puree can be used in bread technology after heat treatment. The possibility of introducing 5 to 25 % of puree in bread technology has been proven.…”
Section: Devising the Recipe For A Cake With Fresh Sliced Pumpkin Acc...mentioning
confidence: 99%